2015
DOI: 10.1103/physrevd.92.115014
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the muong2, a 125 GeV Higgs boson, and dark matter in gauge mediation models

Abstract: We present a class of models in the framework of gauge mediation supersymmetry breaking where the standard model is supplemented by additional U(1) symmetry which acts only on the third generation fermions. The messenger fields carry nontrivial U(1) charge and are vector-like particles under this symmetry. This leads to additional contribution to the soft supersymmetry breaking mass terms for the third generation squarks and sleptons. In this framework we show that the muon g − 2 anomaly, the observed 125 GeV … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…As an alternative, one can resolve the (g − 2) µ discrepancy by extending the particle content of the MSSM with vector-like (VL) matter, as investigated, e.g., in [29][30][31][32][33][34][35][36][37]. The introduction of VL superfields in the superpotential brings along extra degrees of freedom without spoiling the successful unification of gauge interactions at the GUT scale [38].…”
Section: Contentsmentioning
confidence: 99%
“…As an alternative, one can resolve the (g − 2) µ discrepancy by extending the particle content of the MSSM with vector-like (VL) matter, as investigated, e.g., in [29][30][31][32][33][34][35][36][37]. The introduction of VL superfields in the superpotential brings along extra degrees of freedom without spoiling the successful unification of gauge interactions at the GUT scale [38].…”
Section: Contentsmentioning
confidence: 99%
“…Note that in the GMSB scenario additional contributions from non-zero D term associated with flavor U (1) B−L symmetry to the sfermion SSB mass terms were studied in ref. [24]. The A-terms in our scenario vanish at the messenger scale, which is very common in GMSB models (except when the MSSM and messenger fields are mixed [25], which we do not consider in this study).…”
Section: Essential Features Of the Modelmentioning
confidence: 94%
“…There have also been alternative solutions as for example, adding vector-like (VL) matter to MSSM which has been studied in Refs. [23][24][25][26][27][28][29][30][31][32]. The presence of new VL sector gives extra contribution to (g − 2) µ by introducing new sources of smuon mixing and new Yukawa couplings [32].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of new VL sector gives extra contribution to (g − 2) µ by introducing new sources of smuon mixing and new Yukawa couplings [32]. Apart from (g − 2) µ , it has been shown that VL colored sparticles provide extra contributions to Higgs mass [33][34][35][36][37][38] and several phenomenological analyses have addressed the extra VL matter in the context of various long-standing theoretical issues related to beyond SM physics [23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%